IMPACT OF CONSTRUCTION ACTIVITIES ON RESIDENTS OF CAPE COAST NORTH METROPOLIS, GHANA - Zakari Mustapha; Benjamin Boahene Akomah; S. K. Ansah; Chris Kurbom Tieru; Daniel Botchwey Asiedu; Isaac Acquah (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2024)
Construction projects have caused significant disruption in urban areas. Despite the need to limit the environmental impacts of construction operations, stakeholders often fall short, resulting in negative consequences for nearby residents. Aim: This study aimed to investigate the effects of various construction activities on residents of the UCC and CCTU campuses in the Cape Coast North Metropolis, Ghana. Methodology and Results: Using a stratified and random sample of 100 residential houses from the University of Cape Coast and Cape Coast Technical University, questionnaires were administered to residents in university-owned dormitories, private hostels, and faculty/staff housing. Data were analysed using Excel and IBM SPSS, focusing on modelling the relationship between variables and assessing their influence. The results indicated that construction operations impacted the environment and residents of the Cape Coast North Metropolis. The R and R Square values indicated that construction activities affected residents' responses. Meanwhile, the adjusted R Square accounted for the complexity of the model, with a standard error measuring the average prediction error. The constant term was considered significant, representing the expected value when all predictors were zero. Conclusion, significance, and impact: From initial ground disturbance to eventual decommissioning, construction projects can lead to soil degradation, habitat destruction, and increased carbon emissions. There is a need to prioritise sustainable and resident-friendly construction practices by incorporating responsible construction methods that mitigate the negative impacts on both residents and the environment. Continuous evaluation will enable better management and improvement of construction processes, leading to stakeholder benefits. Policymakers should explore eco-friendly building techniques, considering construction impacts.